Range estimation of electric unicycle using weight sensor - Muhammad Syamil Bin Musa (2023)
Most people especially EV’s driver suffer from range anxiety which become the obstacle to the acceptance of electric vehicles, caused by the uncertainty upon the energy level of the battery. Most estimation methods to calculate remaining range are not accurate. EV’s user reserve the on-dash remaining range gauge up to an inappropriate value. This paper proposes an improved version of range estimator devices interfaced with real time-varying dynamic parameter sensor, display unit for monitoring purposes and data logger for backup and data analysis. With the four highlighted dynamic parameter to be analysed which are speed, weight, voltage and current, many analytical data can be studied such as aerodynamic force, rolling force and power consumption. This will help to understand the EV architecture and calculation. Thus, enhancing EV range estimation and mitigate range anxiety from the world community.